Biometric Template Protection based on Hill Cipher Algorithm with Two Invertible Keys - Khalaf, Emad Taha; Mohammed, Muamer N.; Kohbalan, Moorthy; Hasan, Raed Abdulkareem (American Scientific Publisher, 2018)
The security of stored templates has become an important issue in biometric authentication systems this because most of the biometric attacks target the biometric database beside the difficulty of issuing the templates again. Thus, to protect the biometric templates it must be encrypted before storing in database. In this paper we proposed an efficient encryption method based on two invertible and random keys to enhance and overcome the weakness of hill cipher algorithm the keys generated using upper triangular matrices with Pseudo-Random Number Generator (PRNG) using two large and random encryption keys. The proposed encryption method provides sufficient security and protection for the biometric templates from attacks, where the experimental results showed high efficiency comparing with the traditional Hill Cipher and existing methods.